Capture and transport of macroparticles in curved plasma duct at low magnetic field in the presence of an electron beam - Bizyukov, A.A.; Sereda, K.N.; Chibisov, A.D.; Romashchenko, E.V.; Kovalenko, V.V. (Вопросы атомной науки и техники, 2014)
The possibility of the macroparticles transport through a magnetic separator due to their capture by the electric field generated inside the duct becomes possible. The conditions are obtained under which transport of the macroparticles by the negative space charge is investigated. It is shown that if there is a space charge in the plasma duct then the interaction of positively charged macroparticles and the negative space charge takes place and as a result, capturing of the macroparticle through the magnetic separator takes place. Изучена возможность транспортировки макрочастиц (МЧ) через магнитный сепаратор в результате их захвата электрическим полем, созданным отрицательным пространственным зарядом. Показано, что при условии существования пространственного заряда в плазмоводе происходит взаимодействие положительно заряженной МЧ и отрицательного пространственного заряда, в результате чего возможно удержание МЧ внутри плазмовода. Определены условия, при которых происходит траспортировка МЧ через сепаратор. Досліджено можливість транспортування макрочастинок (МЧ) крізь магнітний сепаратор у результаті їх захоплення електричним полем, що створюється від’ємним просторовим зарядом. Показано, що за умови існування просторового заряду в плазмоводі відбувається взаємодія позитивно зарядженої МЧ та негативного просторового заряду, внаслідок чого стає можливим утримання МЧ всередині плазмовода. Здобуто умови, за яких відбувається транспортування МЧ крізь магнітний сепаратор.